Hyposplenism in inflammatory bowel disease. Issue 1 (January 1978) - Ryan, F P; Smart, R C; Holdsworth, C D; Preston, F E
Abstract : Splenic function was assessed in 35 patients with ulcerative colitis and 20 patients with Crohn's disease. Hyposplenism was diagnosed if there were Howell-Jolly bodies in the peripheral blood film or if there was prolongation of clearance from the peripheral blood of injected 51-Cr-labelled heat-damaged red blood cells. Thirteen of the patients with ulcerative colitis had hyposplenism as compared with only one patient with Crohn's disease. Conversely, heat-damaged red cell clearance values faster than the normal range were found in six out of the 20 patients with Crohn's disease. Four patients with hyposplenism and ulcerative colitis developed life-threatening septicaemia in the early postcolectomy period, two of these being further complicated by disseminated intravascular coagulation.